Estimation of replenishable groundwater resources and their utilization status in hard rock terrain - TIWARI, ATUL; TRIPATHI, S K; SAXENA, RANI; DUBEY, SUNIL (The Indian Journal of Agricultural Sciences, 2022)
For an efficient management and development of groundwater resources, it is imperative to have a reliable database on groundwater resources. In this regard, present study was conducted during 2015–18 in Mahatma Gandhi Chitrakoot Vishwavidyalaya, Chitrakoot, Satna, Madhya Pradesh, India. Dynamic groundwater resources of study area have been estimated by using the guidelines of the groundwater resources estimation committee (GEC-1997), Ministry of Water Resources, Government of India. In this study, rainwater infiltration factor (RIF) techniques and different conventional norms were used for groundwater recharge estimation. The assessments of groundwater units were categorized based on stage of groundwater development for the year 2016. The annual groundwater draft for all uses such as domestic and irrigation was 5931.54 ha m. The annual groundwater recharge in the study area was 8666.81 ha m and net annual groundwater availability was 8318.85 ha m. The groundwater utilization and stage of groundwater development had also been determined and the overall stage of groundwater development of Babina block was found to be 71.30%. There was no significant rise or fall of water levels during both the pre-monsoon and post-monsoon intervals in the study area. Considering the stage of groundwater development, it has been categorized that Babina block of Jhansi district, a part of Bundelkhand region falls under ‘SAFE’ category of groundwater development with excellent potential for the future groundwater development.